EFFECTIVENESS OF IMPLEMENTING HALAL CERTIFICATION THROUGH SOCIALIZATION AND TRAINING TO MSMEs IN NORTH SUMATRA - Yusriati, Yusriati; Amrizal, Dedi (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study is to find out the extent of understanding and awareness of MSME actors regarding the importance of obtaining halal certificates for the products they produce. This is in line with government policy which requires halal certificates for products to be distributed in Indonesia. The implementation of obtaining halal certificates for this product is unknown due to several reasons, including: lack of information obtained due to lack of socialization, training and assistance in obtaining halal certification for MSMEs in North Sumatra Province have not been carried out. Basically, the halal certification program for products produced by MSMEs is very important as an acknowledgment of the halalness of a product issued by the Halal Product Guarantee Agency (BPJPH) based on a written halal fatwa issued by the Indonesian Ulema Council (MUI). In addition, it must be realized that every halal certification issued is a form of government protection for Muslim consumers in this country. The research method used is descriptive with a case study approach. The type of data analysis used is categorization data analysis to measure the variables studied. The results of this study indicate that the existing MSMEs have not received clear information regarding the management of halal certification, have not received intensive training and assistance in obtaining certificates and have not felt the need to administer halal certification for the products they produce